Degradation of N-nitrosamines and 1, 4-dioxane using vacuum ultraviolet irradiation (UV254+185 nm or UV172 nm). (September 2021) - Fujioka, Takahiro; Kodamatani, Hitoshi; Minh Tran, Hai Duc; Fujioka, Atsushi; Hino, Koki; Yoshikawa, Takumi; Inoue, Daisuke; Ikehata, Keisuke
Abstract: Advanced oxidation processes (AOPs) play a vital role in attenuating contaminants of emerging concern (CECs) during potable water reuse. AOPs are conventionally performed by irradiating with a 254-nm low-pressure (LP) mercury-vapor (Hg) ultraviolet (UV) lamp along with chemical treatment. Compared with UV-C light treatment (200–280 nm), vacuum-UV (V-UV) light treatment (100–200 nm) is advantageous in terms of hydroxyl radical generation without the requirement for chemical treatment. This study assessed the potential of V-UV (172-nm Xe2 excimer or 185 + 254-nm LP-Hg) lamps on the destruction of two major CECs in potable water reuse, namely N -nitrosodimethylamine (NDMA) and 1, 4-dioxane. Direct irradiation using UV254 nm or UV185+254 nm lamps achieved ≥94% removal of N -nitrosamines, including NDMA, at a UV dose of 900 mJ/cm 2 . In contrast, the Xe2 excimer lamp (UV172 nm ) was less effective for N -nitrosamine removal, achieving up to 82% removal of NDMA. The removal of 1, 4-dioxane by V-UV lamps at a UV dose of 900 mJ/cm 2 reached 51% (UV172 nm ) and 28% (UV185+254 nm ), both of which results were superior to that obtained using a conventional UV254 nm lamp (10%). The addition of hydrogen peroxide during UV254 nm or UV185+254 nm irradiation was found to enhance the removal of 1, 4-dioxane, while UV172 nm irradiation without hydrogen peroxide addition still exhibited greater efficiencies than those UV254 nm lamps-based AOPs. Overall, this study demonstrated that the removal of both NDMA and 1, 4-dioxane can be successfully achieved using either a UV254+185 nm lamp with hydrogen peroxide or a UV172 nm Xe2 excimer lamp without hydrogen peroxide. Highlights: Direct photolysis with vacuum-UV was assessed for CEC removal. NDMA removal using a UV254 nm or UV254+185 nm lamp was greater than with UV172 nm . 1, 4-Dioxane removal using a UV172 nm lamp was more pronounced than other lamps. AOP with a UV254 nm or UV254+185 nm lamp enhanced the degradation of 1, 4-dioxane. AOP with a UV254+185 nm lamp achieved the highest removal of NDMA and 1, 4-dioxane.